Why are epilepsy trials failing? Interview with Emilio Perucca. (November 2011) - Perucca, Emilio
Emilio Perucca sits on the Clinical Investigation editorial board and is Chair of Medical Pharmacology, Department of Internal Medicine and Therapeutics, University of Pavia, and Director of the Clinical Centre, National Neurological Institute, Pavia. Perucca is Treasurer of the International League against Epilepsy and Past-President of the Italian League against Epilepsy. He is a member of the advisory/editorial board of many journals, including Epilepsia, Seizure, Epilepsy Research, CNS Drugs and Lancet Neurology . His research interests include the treatment of epilepsy and outcome assessment in epilepsy. Perucca speaks to Laura Harvey at the journal, on the difficulties facing antiepilepsy drug trials today.